MANAGEMENT OF TRAINING AND SKILL DEVELOPMENT ACTIVITIES UNDER SARVA SHIKSHA ABHIYAN (SSA) - GAIROLA, KULDEEP (THE PRIMARY TEACHER, 2013)
Teaching is the only major occupation of man for which we have not yet developed tools that make an average person capable of competence and performance. In teaching we rely on the ‘naturals,’ the ones who somehow know how to teach” Peter Drucker ( Management thinker). Due to this paradigm shift in approach to education during the last decade, the teachers need to be updated and trained for attaining the goals of education in the state’s as well as national perspective. It is in this background that Sarva Shiksha Abhiyan (SSA) had mandated 20 days annual in-service teacher training programme in its framework. Therefore, SPO (SSA, Uttarakhand) organises 20-days annual teacher training for primary and upper primary level teachers